Sudden, Severe, Idiopathic Occlusal Relationship Change Coexisting with Pain-Related Temporomandibular Disorders: A Case Report - Iva Z. Alajbeg; Senka Meštrović; Marko Zlendić; Magda Trinajstić Zrinski; Ema Vrbanović (University of Zagreb. School of Dental Medicine, 2022)
The article presents a case of a young female patient who sought help due to myofascial pain followed by a sudden occlusal change (anterior open bite (AOB)) that occurred shortly after the administration of a soft night guard that had been previously provided by a general dentist. Palpation of the masseter and temporal muscles elicited the presence of familiar pain. After magnetic resonance imaging of temporomandibular joints, which ruled out disc displacement, the final diagnosis was myalgia. Since the patient had myalgia and malocclusion, the therapy included treatment of both conditions. Temporomandibular disorders TMD management included a combination of pharmacotherapy, kinesiotherapy, and a stabilization splint. After TMD symptoms had resolved, the patient underwent an orthodontic evaluation. Cephalometric analysis revealed skeletal class II, retrognathic face, convex profile, and normal vertical growth pattern. Orthodontic treatment included a fixed appliance with vertical intermaxillary elastics. After 19 months of treatment, both sides achieved acceptable occlusion with Class I. Since the patient had myalgia and severe malocclusion, it was important to follow a systematic diagnostic and therapeutic workflow. Although it is impossible to establish a relationship between TMD symptoms and orthodontic therapy, patients who have TMD symptoms should have their pain resolved through a conservative treatment protocol before commencement of orthodontic treatment. The beginning of orthodontic therapy comes into consideration only when the TMD pain resolves.